2004
DOI: 10.1128/jb.186.23.8074-8082.2004
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the PdxY Protein from Escherichia coli

Abstract: The crystal structure of Escherichia coli PdxY, the protein product of the pdxY gene, has been determined to a 2.2-Å resolution. PdxY is a member of the ribokinase superfamily of enzymes and has sequence homology with pyridoxal kinases that phosphorylate pyridoxal at the C-5 hydroxyl. The protein is a homodimer with an active site on each monomer composed of residues that come exclusively from each respective subunit. The active site is filled with a density that fits that of pyridoxal. In monomer A, the ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 22 publications
1
51
0
2
Order By: Relevance
“…This effect of ATP might provide a safety mechanism for mammalian cells to prevent molecules other than vitamin B 6 from binding to the active site under the pre-reaction state, thus blocking their effects on PDXK. Our results revealed that the pyridoxal binding pocket has a surprising ability to accommodate large molecules such as roscovitine that are different from vitamin B 6 , and roscovitine analogs with N 6 modifications show promise as specific inhibitors for PDXK.…”
Section: Fig 3 Pdxk Binds To Immobilized Nmentioning
confidence: 99%
See 4 more Smart Citations
“…This effect of ATP might provide a safety mechanism for mammalian cells to prevent molecules other than vitamin B 6 from binding to the active site under the pre-reaction state, thus blocking their effects on PDXK. Our results revealed that the pyridoxal binding pocket has a surprising ability to accommodate large molecules such as roscovitine that are different from vitamin B 6 , and roscovitine analogs with N 6 modifications show promise as specific inhibitors for PDXK.…”
Section: Fig 3 Pdxk Binds To Immobilized Nmentioning
confidence: 99%
“…We therefore synthesized two roscovitine analogs with modifications designed so that the H-bonding possibility at N 6 would be prevented (Table II). Either methylation on N 6 or replacement of N 6 by an oxygen, leading, respectively, to N 6 -methyl-(R)-roscovitine (2) and O 6 -(R)-roscovitine (4), converted roscovitine to derivatives devoid of protein kinase inhibitory activity (Table II).…”
Section: Crystal Structure Of Pdxk⅐roscovitine Complex: Roscovitinementioning
confidence: 99%
See 3 more Smart Citations